The Influence of Green Accounting and Environmental Performance on Firm Value from the Perspective of Maqashid Shariah: A Study of Companies Listed in the Jakarta Islamic Index from 2021 to 2024 - Linda Nurlita; Rosydalina Putri; Taufiqur Rahman (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of green accounting and environmental performance on firm value and to examine this relationship from the perspective of maqashid shariah. The study employed a quantitative approach using secondary data obtained through documentation methods from companies’ annual reports and sustainability reports. The population of this study consisted of companies listed in the Jakarta Islamic Index during the 2021–2024 period. The research sample was selected using a purposive sampling method, resulting in 13 companies as the research sample. Data analysis was conducted using panel data regression with the assistance of EViews 12 software. The results indicate that green accounting has a positive and significant effect on firm value. Meanwhile, environmental performance has a negative but insignificant effect on firm value. However, simultaneously, green accounting and environmental performance have a positive and significant effect on firm value. These findings suggest that the implementation of proper environmental management and disclosure can enhance investor confidence and support the improvement of firm value. From the perspective of maqashid shariah, the implementation of green accounting and environmental performance reflects corporate responsibility in maintaining public welfare and environmental sustainability.